2017
DOI: 10.1101/240408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Far-UVC light: A new tool to control the spread of airborne-mediated microbial diseases

Abstract: 11Airborne-mediated microbial diseases such as influenza and tuberculosis represent major public 12 health challenges. A direct approach to prevent airborne transmission is inactivation of airborne

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(128 citation statements)
references
References 44 publications
5
110
1
12
Order By: Relevance
“…Previous reports showed that a low dose of 222-nm UV inactivated several viruses, although the treated viruses were aerosolized; 2 mJ/cm 2 of 222-nm UV inactivated >95% of H1N1 aerosolized influenza virus. 14 In addition, 1.7 and 1.2 mJ/cm 2 of 222-nm UV inactivated 99.9% of aerosolized human coronaviruses alpha HCoV-229E and beta HCoV-OC43, respectively. 15 Previous report showed that the viral titer of SARS-CoV-2 was reduced on a plastic plate over time.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous reports showed that a low dose of 222-nm UV inactivated several viruses, although the treated viruses were aerosolized; 2 mJ/cm 2 of 222-nm UV inactivated >95% of H1N1 aerosolized influenza virus. 14 In addition, 1.7 and 1.2 mJ/cm 2 of 222-nm UV inactivated 99.9% of aerosolized human coronaviruses alpha HCoV-229E and beta HCoV-OC43, respectively. 15 Previous report showed that the viral titer of SARS-CoV-2 was reduced on a plastic plate over time.…”
Section: Discussionmentioning
confidence: 97%
“…The lamp contains an optical filter that removes essentially all but the dominant 222-nm emission wavelength. [9][10][11][12][13][14][15] For 222-nm UVC irradiation, the Care222 was placed 24 cm above the surface of the plates, and the radiation intensity at the surface of the plates was 0.1 mW/cm 2 , as measured with a recently calibrated Unimeter SNK005 meter (Ushio Inc., Tokyo, Japan). After irradiation for each treatment time, the control and treated plates were washed with 1 mL of phosphate-buffered saline for 1 minute and the virus-containing phosphate-buffered saline was collected in a test tube for analysis.…”
Section: -Nm Uvc Disinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are thermolabile; decreased sunlight, low temperatures and less humidity seem to be favourable for COVID-19 (1) . Although natural UV (UV-C) from the sunlight may not be strong enough to kill COVID-19, its antimicrobial efficacy has long been shown to inactivate, thus preventing the transmission of airborne-mediated infections such as influenza and tuberculosis (51) . Further, UV-B from the sun can induce endogenous synthesis of vitamin D in the skinbeing the main source of vitamin D other than the dietary intake or supplementation.…”
Section: Coronavirus Disease and Vitamin D Deficiencymentioning
confidence: 99%
“…This lamp source is an important agent against drug-resistant bacteria and airborne aerosolized viruses. Nevertheless, very low level of UVC can inactivate more than 95% of aerosolized H1N1 influenza virus [24,25].…”
Section: Introductionmentioning
confidence: 99%